3-hydroxypyruvate substitutes for pyridoxine in serC mutants of Escherichia coli K-12. - Shimizu, S (1978)
Escherichia coli K-12 mutants with serC genotype required pyridoxine and serine for normal growth, as do E. coli B mutants of this type. Mutants of the K-12 strain, however, reverted easily to pyridoxine independence without regaining activity in the 3-phosphoserine oxoglutarate transaminase coded for by the serC gene. Both these revertants and the parental type synthesized pyridoxine in normal amounts when 3-hydroxypyruvate was used as a supplement, although neither of these mutants could use this compound to satisfy their serine requirement. Since serine alone was inadequate to provide the nutritional requirement of serC mutants, these mutants must have been unable to synthesize 3-hydroxypyruvate from serine. We suggest that 3-phosphoserine oxoglutarate transaminase in normal E. coli serves as a catalyst for transaminating small amounts of serine to 3-hydroxypyruvate, which is then used in pyridoxine biosynthesis. In serC mutants, this activity is blocked, and these mutants then show a double requirement for serine and pyridoxine.